2023
DOI: 10.3390/ma16072924
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Chemical Hydrogen Storage: Energetics of Liquid Organic Hydrogen Carrier Systems Based on Methyl-Substituted Indoles

Abstract: Liquid organic hydrogen carriers can store hydrogen in a safe and dense form through covalent bonds. Hydrogen uptake and release are realized by catalytic hydrogenation and dehydrogenation, respectively. Indoles have been demonstrated to be interesting candidates for this task. The enthalpy of reaction is a crucial parameter in this regard as it determines not only the heat demand for hydrogen release, but also the reaction equilibrium at given conditions. In this work, a combination of experimental measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…The thermochemical cycle of hybrid sulfur and hydrogen sulfide and two processes in which the thermal separation of sulfuric acid at 855 • C in an unidentified recipient reactor at 1250 with or without a catalyst were determined. The hybrid sulfur process uses electrolysis to resume the production of sulfuric acid and pure hydrogen [10].…”
Section: Thermochemical Solar Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermochemical cycle of hybrid sulfur and hydrogen sulfide and two processes in which the thermal separation of sulfuric acid at 855 • C in an unidentified recipient reactor at 1250 with or without a catalyst were determined. The hybrid sulfur process uses electrolysis to resume the production of sulfuric acid and pure hydrogen [10].…”
Section: Thermochemical Solar Cyclesmentioning
confidence: 99%
“…Concentrated solar radiation is a valuable heat source for solar thermal processes, which involve central receivers and reactors. These processes offer the advantage of low emissions of polluting gases [1][2][3][4][5][6][7][8][9][10][11]. In Table 1 data on the cost price of hydrogen in 2022 are presented [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [59], the authors Vostrikov et al [59] demonstrated the efficiency of liquid organic hydrogen carriers. The authors suggest that this method of hydrogen storage is safe and has a denser form due to the peculiarities of covalent bonds.…”
Section: Introductionmentioning
confidence: 99%